NADPH and Mito-Apocynin Treatment Protects Against KA-Induced Excitotoxic Injury Through Autophagy Pathway - Liu, Na; Lin, Miao-Miao; Huang, Si-Si; Liu, Zi-Qi; Wu, Jun-Chao; Liang, Zhong-Qin; Qin, Zheng-Hong; Wang, Yan (Frontiers in Cell and Developmental Biology, 2021)
Aim Previous research recognizes that NADPH can produce reduced glutathione (GSH) as a coenzyme and produce ROS as a substrate of NADPH oxidase (NOX). Besides, excessive activation of glutamate receptors results in mitochondrial impairment. The study aims at spelling out the effects of NADPH and Mito-apocynin, a NOX inhibitor which specifically targets the mitochondria, on the excitotoxicity induced by Kainic acid (KA) and its mechanism. Methods The in vivo neuronal excitotoxicity model was constructed by stereotypically injecting KA into the unilateral striatum of mice. Administrated NADPH (i.v, intravenous) 30 min prior and Mito-apocynin (i.g, intragastric) 1 day prior, respectively, then kept administrating daily until mice were sacrificed 14 days later. Nissl staining measured the lesion of striatum and survival status of neurons. Cylinder test of forelimb asymmetry and the adhesive removal test reflected the behavioral deficit caused by neural dysfunction. Determined Total superoxide dismutase (T-SOD), malondialdehyde (MDA), and GSH indicated oxidative stress. Western blot presented the expression levels of LC3-II/LC3-I, SQSTM1/p62, TIGAR, and NOX4. Assessed oxygen consumption rate using High-Resolution Respirometry. In vitro, the MitoSOX Indicator reflected superoxide released by neuron mitochondria. JC-1 and ATP assay Kit were used to detect mitochondrial membrane potential (MMP) and energy metabolism, respectively. Results In this study, we have successfully established excitotoxic model by KA in vivo and in vitro. KA induced decreased SOD activity and increased MDA concentration. KA cause the change of LC3-II/LC3-I, SQSTM1/p62, and TIGAR expression, indicating the autophagy activation. NADPH plays a protective role in vivo and in vitro. It reversed the KA-mediated changes in LC3, SQSTM1/p62, TIGAR, and NOX4 protein expression. Mito-apocynin inhibited KA-induced increases in mitochondrial NOX4 expression and activity. Compared with NADPH, the combination showed more significant neuroprotective effects, presenting more neurons survive and better motor function recovery. The combination also better inhibited the over-activated autophagy. In vitro, combination of NADPH and Mito-apocynin performed better in restoring mitochondria membrane potential. Conclusion In summary, combined administration of NADPH and NOX inhibitors offers better neuroprotection by reducing NADPH as a NOX substrate to generate ROS. The combined use of NADPH and Mito-apocynin can better restore neurons and mitochondrial function through autophagy pathway.